Identification of Genes in a Partially Resistant Genotype of Avena sativa Expressed in Response to Puccinia coronata Infection - Loarce, Yolanda; Navas, Elisa; Paniagua, Carlos; Fominaya, Araceli; Manjón, José L.; Ferrer, Esther (Frontiers in Plant Science, 2016)
Cultivated oat (Avena sativa), an important crop in many countries, can suffer significant losses through infection by the fungus Puccinia coronata, the causal agent of crown rust disease. Understanding the molecular basis of existing partial resistance to this disease might provide targets of interest for crop improvement programs. A suppressive subtractive hybridization (SSH) library was constructed using cDNA from the partially resistant oat genotype MN841801-1 after inoculation with the pathogen. A total of 929 genes returned a BLASTx hit and were annotated under different GO terms, including 139 genes previously described as participants in mechanisms related to the defense response and signal transduction. Among these were genes involved in pathogen recognition, cell-wall modification, oxidative burst/ROS scavenging, and abscisic acid biosynthesis, as well genes related to inducible defense responses mediated by salicylic and jasmonic acid (although none of which had been previously reported involved in strong responses). These findings support the hypothesis that basal defense mechanisms are the main systems operating in oat partial resistance to P. coronata. When the expression profiles of 20 selected genes were examined at different times following inoculation with the pathogen, the partially resistant genotype was much quicker in mounting a response than a susceptible genotype. Additionally, a number of genes not previously described in oat transcriptomes were identified in this work, increasing our molecular knowledge of this crop.